2010
DOI: 10.1002/pssr.201004069
|View full text |Cite
|
Sign up to set email alerts
|

Self‐organized nucleation layer for the formation of ordered arrays of double‐walled TiO2 nanotubes with temperature controlled inner diameter

Abstract: It is proposed to use the variation of the electrolyte temperature to fabricate titania nanotubes with variable inner diameter at a constant outer diameter and an invariable package density. The anodization of Ti sheets in an ethylene glycol and HF containing electrolyte is found to allow the preparation of nanotubes with the inner diameter controlled in the range from 10 nm to more than 250 nm through the change of the electrolyte temperature from –20 °C to +50 °C. The peculiarities of the anodization process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…We conclude that the spectral transmission and reflection of nanotube arrays with both open and closed ends can be explained (when the wavelength is large compared to the mean nanotube diameter) by the eikonal approximation using an effective refractive index that is constant across the plane at a given depth in the nanotube array and vary slowly with distance along the nanotube axis. This conical nanotube geometry is consistent with the widely reported [21][22][23][24][25][26][27] observation that anodic nanotube wall thickness varies as a function of length as can be seen for the samples we studied here in Figure 1. However, when the wavelength is comparable to the nanotube diameter we find that the observed wavelength dependence of the reflection coefficient from the closed and open sides can be explained by disorder scattering inside the nanotube array.…”
Section: Introductionsupporting
confidence: 92%
“…We conclude that the spectral transmission and reflection of nanotube arrays with both open and closed ends can be explained (when the wavelength is large compared to the mean nanotube diameter) by the eikonal approximation using an effective refractive index that is constant across the plane at a given depth in the nanotube array and vary slowly with distance along the nanotube axis. This conical nanotube geometry is consistent with the widely reported [21][22][23][24][25][26][27] observation that anodic nanotube wall thickness varies as a function of length as can be seen for the samples we studied here in Figure 1. However, when the wavelength is comparable to the nanotube diameter we find that the observed wavelength dependence of the reflection coefficient from the closed and open sides can be explained by disorder scattering inside the nanotube array.…”
Section: Introductionsupporting
confidence: 92%
“…they showed a considerable degree of inhomogeneity and were limited to tubes with length of about 500 nm. Later work showed significantly improved control over length, diameter, ordering and composition by the use of pH mediation 116 , and particularly by the introduction of non-aqueous electrolytes 117,118,119 . It is noteworthy that fluoride based electrolytes were then also found to be an extremely versatile tool to grow ordered anodic oxide nanostructures on other metals, such as Hf, 120,121 Zr, [122][123][124][125][126][127] Fe, [128][129][130] , Nb, 131,132 V, 133 W, [134][135][136][137] Ta, [138][139][140][141][142] Co, 143 and even Si [144][145][146] .…”
Section: Self-organizing Anodic Tio 2 Nanotube Arraysmentioning
confidence: 99%
“…Fig. 3g shows some typical morphologies of TiO2 synthesized via the anodic oxidation method [135][136][137]. By controlling the synthesis parameters, such as pH value and types of electrolyte, and the addition of active ions or salts, nanoporous TiO2 layers with thickness to the order of several 10 μm and channel diameter from several nanometers to several tens of nanometers can be obtained.…”
Section: Electrochemical Growth Of 1d Nanostructuresmentioning
confidence: 99%
“…By controlling the synthesis parameters, such as pH value and types of electrolyte, and the addition of active ions or salts, nanoporous TiO2 layers with thickness to the order of several 10 μm and channel diameter from several nanometers to several tens of nanometers can be obtained. It was found that the anodization of Ti sheet in an ethylene glycol and HF containing electrolyte allows the preparation of nanotubes with inner diameters controlled in the range from 10 nm to more than 250 nm through changing the electrolyte temperature from −20 to 50°C [135]. Shin et al [132] first prepared self-ordered porous SnO2 using an anodic oxidation method.…”
Section: Electrochemical Growth Of 1d Nanostructuresmentioning
confidence: 99%